THE EFFECT OF SWEET CORN (Zea mays saccharata) FORTIFICATION ON THE CHARACTERISTICS OF NILE TILAPIA (Oreochromisniloticus)NUGGET - Candra Arjuna; N. Ira Sari; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis study aims to determine the effect of sweet corn fortification on the characteristics of Nile tilapia(Oreochromisniloticus)nugget. The treatments given consisted of N0 (without sweet corn fortification), N1 (sweet corn 5%), N2 (sweet corn 10%), and N3 (sweet corn 15%). The analysis parameters observed were sensory (appearance, aroma, taste, and texture) and chemical content (water, protein, fat and ash content). Sweet corn fortification of 15% (N3) produced the best tilapia nugget of 80 panelists (100%) with a characteristic rather yellow colored appearance (7.24), the specific spice aroma of fish meat and a strong aroma towards sweet corn (7.41), sweet corn tastewas more specific than fish meat taste (7.32), soft and dense texture (7.53), with a value of water, protein, fat, and ash content was 48.18%, 21.13%, 1.92%,and 1.85%, respectivelyKeywords: Nile tilapia, sweet corn, nugget